Technologies in the Cruise Tourism Services: A Systematic and bibliometric approach - Gonzáles-Santiago, M.; Loureiro, S. M. C.; Langaro, D. (2022 AMA SUMMER ACADEMIC CONFERENCE, 2022)
COVID-19 and the faster evolution of emerging technologies forced companies to create new business models and become more digital. Therefore, companies worldwide have adopted different digital technologies such as online stores, digital assistants, digital panels, or robotic services. This trend has also impacted the cruise industry, with new cruise ships using digital technologies onboard such as: Artificial Intelligence (AI): ⎼ ZOE digital assistance is used in the latest MSC Cruise Ships. ⎼ Virtual Concierge app used on the newest Celebrity Cruises Ships. ⎼ Robotic bartender at the Bionic Bar on Royal Caribbean Cruise Lines. ⎼ Pepper, the humanoid robot at Costa Cruise Line ships. ⎼ Rob the first humanoid robot bartender at MSC Cruise ships. Virtual Reality (VR): ⎼ Shore excursions ⎼ Culinary dining Despite the strong adoption of new technologies in cruise ships, existing studies related to the use of AI, VR, or robots in smart tourism are mostly limited to restaurants, hotels, or airports. Opening an opportunity to develop a systematic and bibliometric review on this topic - Technologies in the cruise tourism services.